Wpływ integracji Polski z Unią Europejską na ceny detaliczne mięsa i wyrobów mięsnych - Grzybowska, Barbara (Influence of Integration of Poland with the European Union on Retail Prices of Meat and Meat Articles, 2005)
The growth of retail prices of food products, including meat, after the integration of Poland with the European Union, was due to gradual approach of domestic prices to the real existing in EU countries. Internal factors also caused rises, which result was the growth of export demand and at the same time the reduction of supply on domestic market.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1070, t. 1, s. 305-309